A panacea to unsustainable consumption? A review of resource caps - Adam Kelly (Global Sustainability, 2024)
Abstract Non-technical summary Many of the most pressing issues of today, such as climate change, habitat destruction, and conflict, are linked to our growing economies and the increasing amount of natural resources needed to maintain them. Current resource management policies focus on using resources more efficiently while maintaining economic growth. However, these policies have been insufficient and alternatives are needed. Resource caps are one such alternative which would directly limit resource consumption and extraction. This first review on the topic covers existing research on resource caps, the practical issues of implementation, and suggests a way forward for future policy and research.